Poly(ethylene glycol) (PEG)-crosslinked poly(vinyl pyridine)–PEG–poly(vinyl pyridine)-based triblock copolymers prepared by RAFT polymerization as novel gel polymer electrolytes. Issue 42 (9th October 2018) - Shin, Inseop; Nam, Jaebin; Lee, Kukjoo; Kim, Eunsoo; Kim, Tae-Hyun
Abstract : A series of triblock copolymers based on poly(vinyl pyridine)–PEG–poly(vinyl pyridine) (PVP–PEG–PVP) with different PEG-to-PVP ratios (1 : 200, 1 : 250, and 1 : 500) were prepared using the RAFT polymerization. Abstract : A series of triblock copolymers based on poly(vinyl pyridine)–PEG–poly(vinyl pyridine) (PVP–PEG–PVP) with different PEG-to-PVP ratios (1 : 200, 1 : 250, and 1 : 500) were prepared using the RAFT polymerization method and further crosslinked with PEG to produce PEG-crosslinked PVP–PEG–PVP triblock copolymers as novel gel polymer electrolytes. The nanostructured morphologies were controlled using the triblock copolymer structure and PEG was introduced both as a Li ion conductor and as a crosslinker on the side chain of the PVP. The resulting PEG-crosslinked PVP–PEG–PVP gel polymer electrolytes showed good thermomechanical properties, together with moderate ionic conductivities exceeding 1.34 × 10 −5 S cm −1 at 25 °C and 2.94 × 10 −4 S cm −1 at 80 °C. The good ionic conductivity and mechanical stability of these newly developed gel polymer electrolytes ensured a high capacity (135 mA h g −1 at the 30 th cycle and a retention of 94.4% of the initial capacity) in a Li battery prepared using the PEG-crosslinked triblock (1 : 200)-based electrolyte films.